Corrosion behaviour of a dental alloy in some beverages and drinks - Duffó, Gustavo Sergio (2009)
The aim of the present work was to perform a systematic study of the effect of several beverages (alcoholic drinks, natural and artificial fruit juices, vinegar, soft drinks, milk) on the corrosion behaviour of an aluminum-bronze dental alloy. Results were compared to those obtained in artificial saliva and in a solution of sodium chloride. The material used was an aluminum-bronze alloy frequently used in Latin-American countries because of its similarity in appearance to the yellow gold alloys and because economic reasons. The investigation was carried out by means of traditional electrochemical techniques: polarization tests, polarization resistance measurements and weight loss tests. The ranking of aggressiveness of the beverages and solutions studied is given by the corrosion rate computed from the weight loss measurements, and it is as follows: artificial saliva, lemon juice, vinegar, 1M NaCl, white wine, red wine and artificial orange juice. The aggressiveness of the different liquids is independent of both the pH and electrical conductivity of the solution. The most aggressive beverage (artificial orange juice) generates a corrosion rate only 1 order of magnitude higher than that of saliva, a difference that is not relevant for the odontological use considering the short time that beverages are in contact with dental alloys in the oral environment.